INDILACT – Extended voluntary waiting period in primiparous dairy cows. Part 1: randomized controlled trial – SOMRS data – calvings, inseminations, parentage, culling, test milkings, lactation yields and yearly yields - Edvardsson Rasmussen, Anna (Swedish University of Agricultural Sciences, 2022)
The objective of the study is to investigate how an extended voluntary waiting period between calving and first insemination in primiparous cows would affect milk production and fertility during their first and second calving interval.
The data is registered between August 2018 to September 2021.
Data from 2 different sources. Access to these data is restricted due to the agreement with the principal owner of the data Växa Sverige.
1. Data (.txt files) from the Swedish Official Milk Recording System, operated by Växa Sverige regarding breed, calvings, inseminations, 305-d lactation yields, test-day yields, and dry-off dates from 16 farms. The inclusion criteria for the farms included herds with >100 dairy cows in production and a herd average milk production of at least 9 000 kg ECM/cow/year, a mean CI of < 14 months, and a system for daily milk yield registration.
2. Daily milk yields from the milking systems on the farms (three different types of systems: DeLaval, Lely and GEA), Excel files.
Metadata available:
One file with metadata, describing the data processing steps for each category of data, is provided. Also available are Code-lists for reading the data from the text files and for decoding the codes in the text files. R scripts with statistical calculations are also available.
.txt files with information about calvings, cullings, inseminations, parentage. Registered by Farm owners, staff, and animal health staff and .txt files with information about test milkings, lactation yields and yearly yields. Registered by Farm owners, and Eurofins lab.
Variables:
1. Calvings: FarmID, cow-ID, birth year, calving date, easy/difficult calving, calf sex, calf-ID, calf use, calving number
2. Parentage: FarmID, cow-ID, birth date, sex, father ID, father farm ID, birth year father, father breed, milk-index father, mother ID, mother farm ID, birth year mother, mother breed, milk-index mother, grandfather-ID, grandfather-farm ID, birth year grandfather-, grandfather-breed, milk-index grandfather
3. Inseminations: FarmID, cow-ID, insemination date, ear number used bull, pregnancy diagnosis, pregnancy diagnosis date
4. Culling: FarmID, cow-ID, in date (bought to the farm or birth), culling date, culling reason 1-3
5. test milking: FarmID, Cow-ID, birth year, Test milking date, kg milk, % fat, % protein, somatic cell count (SCC), urea, udder health cathegory
6. 305-day lactation yield: FarmID, Cow-ID, birth year, calving date, calving number, kg milk, kg fat, kg protein, farm breed mean kg fat, farm breed mean kg protein.
7. Dry-off date: FarmID, Cow-ID, dry-off date

Studien syftar till att undersöka hur en förlängd frivillig väntetid mellan kalvning och första insemination påverkar mjölkproduktion och fertilitet för förstakalvare under deras första och andra kalvningsintervall.
Data registrerades mellan augusti 2018 och september 2021.
Det finns data från två olika källor. Tillgången till dessa data är begränsad på grund av avtal med ägaren av data (Växa Sverige).
1. Data (.txt filer) från Kokontrollen som sköts av Växa Sverige gällande ras, kalvningar, inseminationer, 305-dagarsavkastning, provmjölkningar och sindatum från 16 gårdar. Inklusionskrieterier för gårdarna var > 100 kor i produktion, samt medelavkastning på minst 9 000 kg ECM/ko och år, medel KI på < 14 månader samt att de skulle ha ett system för daglig mjölkmängdsregistrering.
2. Excelfiler med data från gårdarnas egna mjölkningssystem (DeLaval, Lely och GEA) med dagliga mjölkmängder (från tre olika system: DeLaval, Lely och GEA).
Metadata (tillgängligt):
En metadatafil för respektive kategori av data har skapats med beskrivning av databearbetningen. Dessutom finns kodnycklar för hur koderna i textfilerna ska läsas ut samt kodlista för koder som använts i textfilerna. R-skript med statistisk analys finns också tillgängliga.
.txt files med information om kalvningar, inseminationer, härstamning, utslagning. Registrerade av djurägare, djurskötare och djurhälsopersonal, samt .txt filer med information från provmjölkningar samt laktationsavkastningar och sinläggningsuppgift. Registreringar gjorda av djurägare och Eurofins lab.
Variabler:
1. Kalvningar: GårdsID, ko-ID, födelseår, kalvningsdatum, lätt/svår kalvning, kön på kalven, kalv-ID, kalvens anvndning, kalvningsnummer
2. Härstamning: GårdsID, ko-ID, födelsedatum, kön, fader-ID, faders gårds-ID, födelseår fader, fader ras, mjölkindex fader, moder-ID, moder-ID, födelseår moder, moder ras, mjölkindex moder, morfar-ID, morfar gårds-ID, födelseår morfar, morfarras, mjölkindex morfar
3. Semin: GårdsID, ko-ID, semindatum, öronnummer använd tjur, dräkdighetsdiagnos, dräkdighetsdiagnosdatum
4. Utslagning: GårdsID, ko-ID, ingångsdatum, utgångsdatum, utslagningsorsak 1-3
5. Provmjölkning: GårdsID, Ko-ID, födelseår, provmjölkningsdatum, kg mjölk, fetthalt, proteinhalt, celltal, urea, juverhälsoklass
6. 305-dagars Laktationsavkastning: GårdsID, Ko-ID, födelseår, kalvningsdatum, kalvningsnummer, kg mjölk, kg fett, kg protein, rasmedeltal kg fett i besättningen, rasmedeltal kg protein i besättningen.
7. Sinuppgift: GårdsID, Ko-ID, datum för sinläggning
INDILACT – Förlängd frivillig väntetid för förstakalvare. Del 1: randomiserad kontrollerad studie – kokontrolldata – kalvningar, inseminationer, härstamning, utslagning
INDILACT - Part 1
Keywords: milk production; fertility; dairy cattle; dairy cow; dairy farm; reproduction; artificial insemination (animals); insemination (djur); lactation; laktation; extended; förlängd; extended lactation; förlängd laktation; calving interval; kalvningsintervall; voluntary waiting period; frivillig väntetid; extended calving interval; förlängt kalvningsintervall; extended voluntary waiting period; förlängd frivillig väntetid; cow; ko; lactation yield; laktationsavkastning; services per conception; inseminationer per dräktighet; first service conception rate; dräktig vid första insemination; Animal and Dairy Science; Husdjursvetenskap